Municipal governance and planning toward addressing housing problems to improve access to adequate housing in Maseru and Johannesburg: an exploratory factor analysis - Mphanya, Ramapulane; Gumbo, Trynos; Onatu, George; Ogra, Aurobindo (Frontiers in Sustainable Cities, 2025)
Both Lesotho and South Africa inherited British and apartheid spatial planning, which leveraged on segregation of the urban poor specifically black Africans from the cities to the urban periphery and this has resulted in multiple housing inadequacies. The primary focus is on Maseru and Johannesburg which are the economic capitals of Lesotho and South Africa, respectively. The two cities are experiencing rapid immigration of people who are in search of job opportunities. This scenario is followed by the need for housing, especially for low-income earners. The researchers aimed to explore factors determining the scale of municipal strategies in the development of adequate housing. Specifically, it aims to identify the scale to which the authorities apply an effort in implementing the planning strategies to address the housing problems and improve access to adequate housing. An Exploratory Factor Analysis (EFA) research method was used, factor rotation was done through varimax rotation, the results were validated through a Kaiser-meyer olkin and Bartletts test. The study participants included the 201 residents in Qoaling and 201 residents in Diepsloot experiencing the housing problems and conditions under the city of Johannesburg metropolitan municipality and Maseru Municipal Council, the participants were selected through a purposive sampling technique Result of the findings shows that the environmental conditions in both study areas are different in extent. Whereas in Maseru there are no formal land use plans and regulation, hence the people practice informal subdivision of land which results to informal settlements. The study recommends that municipalities should strengthen access to basic infrastructure and improve waste management techniques which are identified by the residents in both contexts as one of the key issues affecting the housing adequacy. The study goes beyond the descriptive analysis of housing inadequacies as it reveals the structure of these challenges by exploring the patterns of the constructs.